O tym, co ważne w ocenie artykułów, projektów badawczych i wniosków awansowych w naukach społecznych - Brzeziński, Jerzy (Nauka. Biuro Upowszechniania i Promocji Nauki PAN, 2014)
The peer review of scientific manuscripts, grant proposals, dissertations etc. is a cornerstone of modern science and medicine. Different organizations and journals rely on expert and objective review by knowledgeable researchers to ensure the quality of the research conducted by scientists. Moreover, the recommendations the reviewers make and the advice they give to authors set the scientific standards of the discipline. The review of manuscripts, grant proposals and other documents of this kind raises many ethical issues and problems. The reviewer should be aware of these when deciding whether to accept proposal to prepare a review. This paper describes some of the formal regulations as well as ethical issues that can arise during the review process and discusses their implications.
Keywords: review policies; ethics of review; conflict of interest; competence; morality